1999
DOI: 10.1111/j.2042-3306.1999.tb05175.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omeprazole paste on healing of spontaneous gastric ulcers in horses and foals: a field trial

Abstract: Summary A multicentre, blinded, randomised complete‐block, field trial was conducted with 140 horses and foals age 4 weeks‐28 years to determine if omeprazole paste is effective and safe in promoting healing of spontaneous gastric ulcers under a variety of field conditions and in different breeds and ages of horses. Horses in the study had gastric ulceration as determined by gastroscopy and were divided into replicates of 4 or 5 animals. One horse in each replicate was assigned randomly to receive an empty ome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 15 publications
5
58
2
2
Order By: Relevance
“…The findings relating to the efficacy of omeprazole at day 30, concur with previous work [13,14,[29][30][31]. However, this is the first study, to the author's knowledge that has identified a reduced efficacy of omeprazole after more than 2-months of treatment.…”
Section: Discussionsupporting
confidence: 75%
“…The findings relating to the efficacy of omeprazole at day 30, concur with previous work [13,14,[29][30][31]. However, this is the first study, to the author's knowledge that has identified a reduced efficacy of omeprazole after more than 2-months of treatment.…”
Section: Discussionsupporting
confidence: 75%
“…Spontaneous improvement rates of 32% compared to 99% improvement in horses treated with omeprazole were found after 28 days in a similar study. The overall healing rate was 8.9% and 87% respectively in the control and omeprazole treated groups in the same study [11]. In that study the personnel that administered the medication was not able to observe the examination.…”
Section: Discussionmentioning
confidence: 95%
“…The proton pump inhibitor omeprazole has been found safe and highly efficient in both treating and preventing recurrence of gastric ulcers in horses [8-11] at dose ranges from 1–4 mg/kg. Comparison of omeprazole and histamine 2 antagonists shows superior effect of omeprazole [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the lesion type omeprazole is recommended as the treatment of choice [1] and is widely used for this purpose. Its efficacy in the treatment of ESGD in a number of clinical studies [4][5][6] appeared to support this conclusion. Its efficacy in the treatment of ESGD in a number of clinical studies [4][5][6] appeared to support this conclusion.…”
Section: Introductionmentioning
confidence: 85%